2020
DOI: 10.3390/nu12051392
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Vitamin D-Dependent Apoptosis in Obesity

Abstract: The role of vitamin D in obesity appears to be linked to vitamin D insufficient/deficient status. However, mechanistic understanding of the role of vitamin D in obesity is lacking. We have shown earlier that the vitamin D hormonal form, 1,25-dihydroxyvitamin D3 (1,25(OH)2D3), induces cell death by apoptosis in mature adipocytes. This effect of the hormone is mediated by the cellular Ca2+ signaling pathway: a sustained increase of intracellular (cytosolic) Ca2+ concentration followed by activation of Ca2+-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
0
26
0
2
Order By: Relevance
“…As fibers are involved in the modulation process of inflammation, immune system and microbiota equilibrium [ 22 ], fiber consumption from fruits and whole grains was significantly increased with respect to the baseline (LIPPY and CTRL: p < 0.0001). The mMeD content of molecules with antioxidant and anti-inflammatory activity [ 32 ] such as vitamins A (LIPPY and CTRL: p < 0.05), C (LIPPY: p < 0.0001, CTRL: p < 0.05), D (LIPPY and CTRL: p < 0.05) and minerals [ 40 , 41 , 42 ] was significant increased with respect to the baseline, with amelioration of the MAI index (LIPPY and CTRL: p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…As fibers are involved in the modulation process of inflammation, immune system and microbiota equilibrium [ 22 ], fiber consumption from fruits and whole grains was significantly increased with respect to the baseline (LIPPY and CTRL: p < 0.0001). The mMeD content of molecules with antioxidant and anti-inflammatory activity [ 32 ] such as vitamins A (LIPPY and CTRL: p < 0.05), C (LIPPY: p < 0.0001, CTRL: p < 0.05), D (LIPPY and CTRL: p < 0.05) and minerals [ 40 , 41 , 42 ] was significant increased with respect to the baseline, with amelioration of the MAI index (LIPPY and CTRL: p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that Ca 2+ is a key player in apoptosis and due to the vitamin D effect on the regulation of intracellular Ca 2+ level, it is suggested that the vitamin is involved in this process [ 206 , 207 , 208 ]. Sergeev et al have proposed a mechanism of intracellular Ca 2+ regulation and apoptosis by calcitriol in obesity.…”
Section: How Does Vitamin D Overcome Insulin Resistance and Relatementioning
confidence: 99%
“…Then, the activation of μ-calpain by the sustained cytosolic Ca 2+ signal was followed by the induction of Ca 2+ /calpain-dependent caspase-12. These activated proteases seem to be sufficient for the execution of apoptosis [ 207 ]. By contrast, Sun et al reported that calcitriol inhibited apoptosis and stimulated the expression of genes that promote the proliferation of human subcutaneous adipocytes [ 192 ].…”
Section: How Does Vitamin D Overcome Insulin Resistance and Relatementioning
confidence: 99%
“…Emerging evidence suggests that vitamin D has a potential to improve insulin sensitivity that would reduce food intake. 30 In addition, in vitro and animal studies have shown that the bioactive form of vitamin D, 1,25-dihydroxyvitamin D can induce mature adipocytes death by apoptosis 32 ; in a high-fat diet-induced obesity mouse model, an increased intake of vitamin D is associated with a decreased weight of white adipose tissue due to induction of apoptosis.…”
Section: Open Accessmentioning
confidence: 99%